Temperature sensitive electricity demand and policy implications for energy transition: a case study of Florida, USA - Fache, Anna; Bhat, Mahadev G. (Frontiers in Sustainable Energy Policy, 2024)
Electricity demand has been increasing due not only to factors like population and GDP growth, but also climate change. The growing uncertainties around future electricity demand and its determining factors will make planning for renewable energy transition very challenging. For robust policy design and planning, it is necessary to have better understanding of how alternative future climate affects the electricity demand. This study projects future monthly electricity demand in the context of Florida, USA, under different climate scenarios, using the degree-day method and an energy consumption regression model, estimated using historical data.. The regression model of historical electricity demand analyzes the impact of variables such as population, employment, GDP, price of electricity, temperature, and daylight hours on the electricity consumption of the residential sector and commercial and industrial sectors in Florida.The above estimated models are basis for projecting the future electricity demands in both sectors. The data on future temperature under alternative climate scenarios were available from a recent regional climate modeling study. The residential sector will see a 63% increase in electricity demand from 2001-2019 to 2050 under the Representative Concentration Pathway (RCP) 4.5 scenario, and 65% increase under the RCP 8.5 scenario. The commercial and industrial sector will register 47% and 54% increase in electricity demand under RCP 4.5 and RCP 8.5, respectively, during the same period. Increases in demand for cooling during summer more than offsets the decreases in demand for heating in winter, particularly for the residential sector. The current renewable energy policies are not adequate to meet the above climate-driven increases in electricity demand. We recommend that a Renewable Portfolio Standard be implemented to increase the share of renewables in the state's electricity mix. The paper makes several policy recommendations to facilitate more sustainable transition to renewable energy and manage extreme heat impacts on people's life.